Recurrence Rates After Microvascular Decompression in Patients With Primary Trigeminal Neuralgia and Its Influencing Factors: A Systematic Review and Meta-Analysis Based on 8,172 Surgery Patients - Chen, Fangyu; Niu, Yuming; Meng, Fan; Xu, Pan; Zhang, Chao; Xue, Yingying; Wu, Shishi; Wang, Long (Frontiers in Neurology, 2021)
Background: Primary trigeminal neuralgia (PTN) is known to reoccur following Microvascular decompression (MVD) surgery. However, the rates and contributing factors related to PTN recurrence remain controversial. The purpose of this study was to explore the postoperative recurrence rates and related influencing factors of patients with PTN after MVD. Additionally, recurrence rates after different treatments were compared to provide guidelines for clinicians. Methods: We conducted systematic reviews and meta-analyses in accordance with the preferred reporting items of the PRISMA guidelines. We searched nine databases, namely, the PubMed, EMBASE, Cochrane Library, Web of Science, CINAHL, CBM, CNKI, VIP, and Wanfang databases, from establishment to July 13, 2020, selecting for studies about the long-term postoperative efficacy of MVD in the treatment of PTN. Factors associated with higher recurrence rates after MVD and long-term postoperative results of other treatments underwent formal meta-analysis, where odds ratios (ORs) with the corresponding 95% confidence intervals (CIs) were calculated. The dose-response model was used to inspect the associations between several factors and higher recurrence rates. Results: Seventy-four studies (8172 patients, 32 case series studies and 42 nonrandomized controlled trials) were analyzed in our research. Overall, 956 out of 8172 patients relapsed, and the pooled recurrence rate was 0.096 (0.080-0.113). Influencing factors of relatively higher recurrence rates included atypical trigeminal neuralgia symptoms, lack of nerve groove, nonarterial compression, patients who were 50-60 years old, and longer disease duration. Dose-response analysis showed that the recurrence rate had a significant trend with the published year and the follow-up time. Simultaneously, the recurrence rate of MVD treatment was much lower than that of conventional drug treatment, gamma knife surgery, percutaneous balloon compression and radiofrequency thermocoagulation. When the surgical technique was improved or combined with partial sensory rhizotomy (PSR), the postoperative recurrence rates were significantly reduced. Conclusions: Even for PTN patients who have a successful operation, approximately 10% of them will still relapse. This research identifies several factors that can affect the recurrence rate. Compared to other operations, MVD has a relatively lower recurrence rate. Our analysis suggests that improved surgical techniques and combining PSR and MVD will yield better results.